Comparative Analysis of Analogue and Digital Methods for Magnetic Flux Estimation in the Core of a Medium-Voltage Voltage Transformer Operating Under Ferroresonance Conditions - Suchorolski, Piotr; Smolarczyk, Adam; Łukaszewski, Piotr; Łapczyński, Sebastian; Szulborski, Michał; Owsiński, Maciej; Łukaszewski, Artur; Kolimas, Łukasz; Nogal, Łukasz (Applied sciences, 2024)
The main objective of the research described in the article was to determine the following: Is it possible to estimate the magnetic flux linkage in the core of a voltage transformer using analogue or digital methods? Will it be possible to estimate it approximately both in the normal state and in the state of deep core saturation (ferroresonant state)? The research aimed to identify the advantages and disadvantages of both proposed estimation methods. As part of the research described in this paper, a simulation model was developed and executed in the MATLAB/Simulink environment to generate a series of secondary voltage and flux waveforms in voltage transformers. The secondary voltage and flux waveforms were modelled under ground fault conditions, initiating ferroresonance oscillations in the medium-voltage network. To determine the associated flux from the simulated secondary voltages of the voltage transformers, an analogue integration circuit, a voltage analogue input circuit and a numerical integration algorithm with offset elimination were developed and implemented in an STM32 microcontroller. The obtained reference flux waveforms were used to verify the accuracy of the estimation of flux waveforms obtained using the analogue and digital methods. As a result, it was determined that both methods allow for a relatively accurate estimation of the periodic component of the magnetic flux. It also presented how both methods respond to the presence of slowly changing (aperiodic) components. Possible applications were proposed in order to create an innovative criterion for detecting ferroresonance oscillations.